MPLEMENTATION OF POS (point of sale) APPLICATIONS IN IMPROVING SERVICES AT KOPERSI INDUK PONDOK PESANTREN NURUL JADID PAITON PROBOLINGGO - Achmad Febrianto (Nurul Jadid University, 2022)
The purpose of POS (point of sale) is to facilitate transactions through a sales-oriented activity and a system. For instance, in service, inventory management, and data on merchandise sales.The purpose of this study was to determine the extent to which the use of POS (point of sale) applications enhances consumer service. As a result of this study's findings, customers can now obtain services more easily through the use of POS (point of sale) applications.So that it can assist in the management of operational activities and improve the efficiency of service processes.With the transition from the manual to the digital mode of operation.It is beneficial for the chief cooperative officers in other service processes to ensure that this POS (point of sale) application can effectively simplify and speed up the service process when consumers are present.It is used to enhance consumer service during the transaction payment process.To enable officers of the central Pondok Pesantren cooperative to provide comprehensive service to students or customers, it is beneficial for the leading cooperative officers to be proficient in other service processes so that the application of this POS (point of sale) application can effectively simplify and speed up the service process in the presence of consumers.It is used to enhance consumer service during the transaction payment process. To enable officers of the leading Pondok Pesantren cooperative to provide complete service to students or customers, it is beneficial for officers of the leading cooperative to be proficient in other service processes so that the application of this POS (point of sale) application can simplify and accelerate the service process effectively when consumers are present. It is used in the transaction payment process to enhance consumer service, allowing the leading Pondok Pesantren cooperative officers to provide comprehensive service to students or customers.